1986
DOI: 10.1007/bf00437168
|View full text |Cite
|
Sign up to set email alerts
|

First culture-proven gastrointestinal entermophthoromycosis in the United States: A case report and review of the literature

Abstract: The zygomycosis are fungal infections often occurring in compromised hosts. We report the first culture-proven case of a gastrointestinal infection in the United States by Basidiobolus haptosporus (ranarum). The clinical and histological features are noted in order to distinguish this infection from the more widely reported mucormycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…GI basidiobolomycosis is rare (Bittencourt et al, 1979;Khan et al, 1998), with only 14 cases in adults (Khan et al, 2001;Lyon et al, 2001) and 12 cases in children (Al Jarie et al, 2003;Wasim Yusuf et al, 2003) having been reported worldwide. The reported cases included eight cases from the United States; eight from the Kingdom of Saudi Arabia, four from Brazil, two each from Nigeria and Kuwait, one from Iran and one from the Netherlands (de Aguiar et al, 1980;Schmidt et al, 1986;Pasha et al, 1997;Khan et al, 1998;Smilack, 1998;Yousef et al, 1999;Zavasky et al, 1999;Al Jarie et al, 2003). No specific risk factors were identified for GI basidiobolomycosis, except that three patients had a history of diabetes mellitus (Khan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…GI basidiobolomycosis is rare (Bittencourt et al, 1979;Khan et al, 1998), with only 14 cases in adults (Khan et al, 2001;Lyon et al, 2001) and 12 cases in children (Al Jarie et al, 2003;Wasim Yusuf et al, 2003) having been reported worldwide. The reported cases included eight cases from the United States; eight from the Kingdom of Saudi Arabia, four from Brazil, two each from Nigeria and Kuwait, one from Iran and one from the Netherlands (de Aguiar et al, 1980;Schmidt et al, 1986;Pasha et al, 1997;Khan et al, 1998;Smilack, 1998;Yousef et al, 1999;Zavasky et al, 1999;Al Jarie et al, 2003). No specific risk factors were identified for GI basidiobolomycosis, except that three patients had a history of diabetes mellitus (Khan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These infections have been reported primarily in healthy patients (four of five cases), but in one case the patient was diabetic and anergic (110,411). The stomach, duodenum, and colon are the primary sites of gastrointestinal involvement, and granulomatous inflammation and fibrosis are limited to the muscularis propria with no vascular invasion in any of the patients (359).…”
Section: Entomophthorales Causing Zygomycosis In Humansmentioning
confidence: 96%
“…The exact reverse of this is true for Conidiobolus and Basidiobolus infections. Disease occurs primarily in normal, immunocompetent hosts (184,442), with relatively few cases currently seen associated with immuncompromise (214,411,486,487).…”
Section: Relationship Of the Entomophthorales To The Mucoralesmentioning
confidence: 99%
“…In 1986, the first culture-proven case of GIB in the USA was reported by Schmidt and his colleagues (Schmidt et al, 1986). The patient was a 69-year-old diabetic man with lesions involving the duodenum, ileum, caecum and ascending colon.…”
Section: Clinical Laboratory Imaging and Histopathological Findingsmentioning
confidence: 99%